SIGNIFICANT ONLINE LEARNING IN THE ERA OF THE COVID-19 PANDEMI - Yustina (eScience Humanity Journal, 2022)
During the spread of the Covid-19 virus was sweeping the world, Indonesia was also affected, especially in the education sector. If usually the teaching and learning process is carried out face to face in the classroom, then as a result of this pandemic the teaching and learning process must be carried out online. The method used is direct observation in the field. The results of the analysis see that the role of information and communication system technology is very important as a medium in implementing online learning with a flexible learning system. This research is Emphasize on learning with the help of information and communication technology platforms. The media that can be used in online learning in the era of the Covid-19 pandemic include WhatsApp, Zoom, Google Classroom (GCR) and other technological media that can support learning activities during the Covid-19 pandemic. Because of the role of the media, this is what makes the writer interested in discussing further the shift from offline to online learning media.